AN ANALYSIS OF EXPRESSIVE SPEECH ACTS USED BY STEVE ROGERS AS THE MAIN CHARACTER IN CIVIL WAR MOVIE - Lalu Banu Sirwan; Yuyun Yulia (JELLT (Journal of English Language and Language Teaching), 2017)
The objective of the study are to describe (1) the kinds of expressive speech act used by Steve Rogers in Civil War movie, and (2) the S-P-E-A-K-I-N-G model used by Steve Rogers in the movie. This research reveals of expressive speech to express the main characterâ€™s feeling, attitude, and emotion. The data were collected by watching the movie and reading the movie script to get information about the utterances that were used by Steve Rogers in Civil War movie. The findings show that there are ten kinds of expressive speech acts in forty five utterances found in the movie and Steve Rogers used S-P-E-A-K-I-N-G model in cultural context; due to in his interaction, he showed care, sympathy and empathy to others.Â